The Comparison of the Effectiveness of Cognitive-Behavioral Therapy with Emotional Intelligence Training on Social Adjustment in Adolescents with Conduct Disorder - Amirkhanloo, Adel; Doosti, Yarali; Donyavi, Reza (Applied Family Therapy Journal (AFTJ), 2022)
Aim: This study was performed to compare the effectiveness of cognitive-behavioral therapy with emotional intelligence training on social adjustment of adolescents with conduct disorder. Method: The present research method was quasi-experimental with pre-test and post-test design with control group (two experimental groups and one control group). The statistical population of the study consisted of all adolescents with conduct disorder who are present in the Tehran Correctional Center in 1398. Samples were screened from subjects with conduct disorder, 45 adolescents were randomly divided into three groups (two experimental groups and one control group of 15 people in each group). Sampling was done purposefully in the selection stage of the subjects and randomly in the replacement stage in the experimental and control groups. The data collection tool in this study was the California Social Adjustment Questionnaire (1953). Multivariate covariance (MANCOVA) test was used to analyze the data. Results: The results showed that cognitive-behavioral therapy and emotional intelligence training are effective in increasing social adjustment of adolescents with conduct disorder (P<0.001). Also, comparison of the two experimental groups showed that cognitive-behavioral therapy has a greater effect on increasing adolescent social adjustment (P<0.001). Conclusion: It can be concluded that cognitive-behavioral therapy and emotional intelligence training are effective in increasing social adjustment of adolescents with conduct disorder.